2019
DOI: 10.1002/ange.201911277
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Long‐Range n to π* Interaction Secures the Smallest known α‐Helix in Water

Abstract: The introduction of an amide bond linking side chains of the first and fifth amino acids forms ac yclic pentapeptide that optimally stabilizes the smallest known ahelix in water.T he origin of the stabilization is unclear.T he observed dependence of a-helicity on the solvent and cyclization linker led us to discover an ovel long-range nt op* interaction between amain-chain amide oxygen and auniquely positioned carbonyl group in the linker of cyclic pentapeptides. CD and NMR spectra, NMR and X-ray structures,mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…We now analyze n → π* interactions, which have been shown to play a role in two scenarios: (i) structure and (ii) reactivity. In the first scenario, this interaction is involved in the stability and preferential conformations of small molecules, peptides, , proteins, , peptoids, ,, and nucleic acids. , In the second scenario, the n → π* interactions resemble the Bürgi–Dunitz trajectory for nucleophilic addition to the carbonyl group . In the following, the second scenario will be analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…We now analyze n → π* interactions, which have been shown to play a role in two scenarios: (i) structure and (ii) reactivity. In the first scenario, this interaction is involved in the stability and preferential conformations of small molecules, peptides, , proteins, , peptoids, ,, and nucleic acids. , In the second scenario, the n → π* interactions resemble the Bürgi–Dunitz trajectory for nucleophilic addition to the carbonyl group . In the following, the second scenario will be analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In the NMR spectra of peptide 1 c, the linker amide NH resonance was also split into a broad doublet of doublets, whereas for 2 c it was a broad triplet, in agreement with the observation by Hoang et al, who proposed specific n!π* stabilizing interaction in a KxxxD lactam-bridged peptide. [14] The corresponding NH resonances were not observable in 3 c and 4 c because of signal overlap.…”
Section: Nmr Data Evidenced the Helical Folding Of C-terminal Helix O...mentioning
confidence: 99%
“…In peptide 1 c, we also observed that the conformation of the lactam was compatible with a n!π* stabilizing interaction involving the linker amide carbonyl π* orbital and the Lys P10 main chain carbonyl n orbital, which was mentioned above (Figure S5). [14] The monocyclic peptides were not co-crystallized, but the v107 peptide:VEGF NMR structure can be used as a model. [8] Despite some sequence differences, all the peptide-protein contacts are equivalent (see Supporting Information for details), except for n Leu 6, which is substituted by a Met in v107.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 2 more Smart Citations